Development of video song-based learning media on English speaking skills phase E students at SMAN 1 Pulau Punjung - Wahyuni, Neni Sri; Nanda, Dodi Widia; Efendi, Raimon (PT The Collaboration UVW, 2024)
This research aimed to see the extent to which students are interested in learning using song videos. The development of song-video-based learning can provide more understanding, insight, and knowledge to students, especially students at SMAN 1 Pulau Punjung so that students can improve their abilities. Skills their English more actively. This research method was carried out using a non-quantitative method associative. The research sample numbered 73 people from 268 phase E students at SMAN 1 Pulau Punjung. Based on the needs analysis questionnaire distributed, it can be concluded that the development of song-video-based learning media was indeed very important and needed following the interest indicator of 94% in the very high category and the need indicator of 92% in the also very high category.